2010
DOI: 10.1523/jneurosci.1562-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

On the Origins of Modularity in Motor Control

Abstract: The control of movement is highly complex because of the biomechanical redundancy of the musculoskeletal system (Bernstein, 1967). To cope with the large number of degrees of freedom, humans and animals likely rely on a modular control architecture. In other words, the CNS may activate flexible combinations of motor primitives instead of controlling each muscle independently, a motor primitive being a premotor drive generated by some neuronal population (for example, in the spinal cord) that recruits a covaryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Finally, approaches based on single-trial analysis of neural activity could also be instrumental in clarifying the existence of a neural basis for the muscle synergies (Hart and Giszter, 2004, 2010; Nazarpour et al, 2012; Ranganathan and Krishnan, 2012). For example, they could in principle be applied to decode the task from single-trial neural population patterns that regulate the activation of synergies, and also to determine which patterns encode task differences, and which carry additional or independent information to that carried by other patterns (Delis et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, approaches based on single-trial analysis of neural activity could also be instrumental in clarifying the existence of a neural basis for the muscle synergies (Hart and Giszter, 2004, 2010; Nazarpour et al, 2012; Ranganathan and Krishnan, 2012). For example, they could in principle be applied to decode the task from single-trial neural population patterns that regulate the activation of synergies, and also to determine which patterns encode task differences, and which carry additional or independent information to that carried by other patterns (Delis et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hart and Giszter (2010) showed that some interneurons of the frog spinal cord were better correlated with temporal synergies than with individual muscles. Therefore, they suggested that these neural populations constitute a neural basis for synergistic muscle activations (Delis et al, 2010). Another study demonstrated that the sequential activation of populations of neurons in the cat's motor cortex initiates and sequentially modifies the activity of a small number of functionally distinct groups of synergistic muscles (Yakovenko et al, 2010).…”
Section: Synergies As Input-space Generatorsmentioning
confidence: 99%
“…We believe that application of our new extraction algorithm to simultaneously recorded neural and muscle activities may allow identifying invariant temporal and spatial neural patterns and relating them explicitly to both primitives (i.e., temporal modules) and muscle synergies (i.e., spatial modules). Hence, modeling neural and EMG data with the space-by-time decomposition may help to uncover the direct link among the different levels of the hierarchical organization of motor control and lead to new insights in the quest of understanding the neural basis of modularity in the control of movements (Bizzi and Cheung 2013;Delis et al 2010).…”
Section: Possible Applications Of the Proposed Model Of Modularitymentioning
confidence: 99%
“…A prominent example of such modularity is given by muscle synergies (D'Avella et al, 2003; Ting and McKay, 2007), loosely defined as stereotyped patterns of coordinated activations of groups of muscles. According to this hypothesis, the muscle patterns driving movements originate from linear combinations of a small number of synergies presumably recruited by a premotor drive generated by some neuronal population (Delis et al, 2010; Hart and Giszter, 2010). …”
Section: Introductionmentioning
confidence: 99%